(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and Objectives: Nutritional anemia is a condition in which hemoglobin content of blood is lower than normal as a result of deficiency of one or more essential nutrients, regardless of the cause of such deficiency To know the awareness and perception about anemia among urban and rural high school girls aged 13-16years, To know their awareness about health impacts of anemia during growth period and pregnancy, To compare the awareness and perception on anemia between urban and rural high school girls, To study the prevalence and severity of anemia among urban and rural high school girls, To study the relationship between the severity of anemia and educational level of Mother. Methods: A school based Cross sectional, comparative study, 650 adolescent high school girls of which 330 were from school of Bhagalpur city & 320 from schools of field practice area of Nathnagar. Conclusion: The present study revealed that rural adolescent girls were more aware about anemia compared to urban girls, where as both urban & rural girls had same perception about anemia. The prevalence of anemia was higher among rural girls compared to urban girls & among girls whose mother had completed primary level of education.